On the Epistemology and Psychology of Speech Comprehension - Dean Pettit (Baltic International Yearbook of Cognition, Logic and Communication, 2009)
How do we know what other speakers say? Perhaps the most natural view is that we hear a speaker's utterance and infer what was said, drawing on our competence in the syntax and semantics of the language. An alternative view that has emerged in the literature is that native speakers have a non-inferential capacity to perceive the content of speech. Call this the perceptual view. The disagreement here is best understood as an epistemological one about whether our knowledge of what speakers say is epistemically mediated by our linguistic competence. The present paper takes up the question of how we should go about settling this issue. Arguments for the perceptual view generally appeal to the phenomenology of speech comprehension. The present paper develops a line of argument for the perceptual view that draws on evidence from empirical psychology. The evidence suggests that a speaker's core syntactic and semantic competence is typically deployed sub-personally (e.g., by something like a module). The point is not just that the competence is tacit or unconscious, but that the person is not the locus of the competence. I argue that standing competence can enter into the grounds for knowledge only if it is subject to a certain sort of epistemic assessment, an assessment that is appropriate only if the person is the locus of that competence. If the person is not the locus of a speaker's core linguistic competence, as the psychological evidence suggests, then that competence does not enter into the grounds for our knowledge of what speakers say. If this line of argument is right, it has implications for the epistemology of perception and for our understanding of how empirical psychology bears on epistemology generally.